THE CONCEPT BEHIND THE TERM “TATARS” IN MEDIEVAL ARABIC WRITINGS OF THE 13th–15th CENTURIES - Sayfetdinova E.G. (Золотоордынское обозрение, 2025)
To study the features of the display, application, and meaning of variations of the term “Tatar” found in medieval Arabic writings of the 13th–15th centuries.Research materials: The main sources of this study are the works of Arabic-languageauthors of the 13th to 15th centuries: Ibn al-Athir, Ibn Abi Hadid, Ibn Abd az-Zahir, an-Nuwayri, Rukn ad-Din Baybars, Ibn Khaldun, al-Maqrizi, etc. Results and novelty of the study: The term “Tatar” was widely used in many medieval sources, as well as in medieval Arabic literature. However, no comprehensive study of the visualization of this term in medieval Arabic sources of the 13th-15th centuries has been conducted. Analysis of the works of Arab scholars of the 13th-15th centuries revealed that, when presenting the history of the Chingizids, the authors who wrote about them at the beginning of the 13th century, not being direct witnesses, let alone eyewitnesses of those events, almost entirely based their concepts on the material of the History of Ibn al-Athir. In the works of Ibn Abi Hadid and Abu Shama al-Maqdisi, the term “Tatar” was used consistently. Later authors, continuing the traditions of their predecessors, relied on their material and borrowed this term, subsequently using it in presenting the entire history of the Chingizids. Along with this, they (An-Nuwayri, Al-Omari, Ibn Khaldun) tried to determine the origin of the medieval Tatars. Beginning from the middle of the 13th century, Arab authors, focusing on the historical realities of their time, used the marker “Mongol” along with “Tatar” in their writings, mainly in relation to the Hulaguids and Jochids. However, the term “Tatar” was used quite widely until the 15th century.